EFFECT OF RHODIUM INFILTRATION ON THE MICROSTRUCTURE AND PERFORMANCE OF Ni/Ce0.8Gd0.2O2-δ CERMET ANODE FOR LOW TEMPERATURE SOLID OXIDE FUEL CELL - F. Torknik; M. Keyanpour-Rad; A. Maghsoudipour; G. M. Choi (Iranian Journal of Materials Science and Engineering, 2016)
In order to further enhance the Ni/Ce 0.8Gd0.2O2-δ (Ni/GDC20) cermet anodic performance for low temperature solid oxide fuel cell (LT-SOFC), a study was conducted on the nanostructuring of NiO/GDC composite by only once wet-infiltration of rhodium chloride precursor. By using electrochemical impedance spectroscopy (EIS) analysis, the effect of only one drop of Rh-infiltrating solution on the anodic polarization resistance was examined using symmetric Ni–GDC20|GDC20|Pt electrolyte-supported cell at 400-600 °C. Nanostructural evolution before and after H 2 reduction at 600 °C and also after anodic performance test was investigated by atomic force microscopy (AFM), field emission scanning electron microscopy (FE-SEM), and transmission electron microscopy (TEM) techniques in comparison to the anode itself. Despite the fine distribution of Rh-infiltrated nanoparticles having average particle size of 11.7 nm, the results showed ineffectiveness and inability of the Rh nanoparticles to succeed in decreasing of anodic polarization resistance for H 2 oxidation reaction in LT-SOFC.